Survey of the water bodies for ecotoxic metals by laser-induced breakdown spectroscopy - Haider, A F M Yusuf; Rahman, Bulu; Khan, Zulfiqar H.; M, Abedin Kazi (© 2015, Mary Ann Liebert, Inc., 2017)
This review was published in the journal Environmental Engineering Science [© 2015, Mary Ann Liebert, Inc.] and the definite version is available at: 10.1089/ees.2014.0170